CSNK2B: A broad spectrum of neurodevelopmental disability and epilepsy severity. - Ernst, Michelle E; Baugh, Evan H; Thomas, Amanda; Bier, Louise; Lippa, Natalie; Stong, Nicholas; Mulhern, Maureen S; Kushary, Sulagna; Akman, Cigdem I; Heinzen, Erin L; Yeh, Raymond; Bi, Weimin; et al. (Epilepsia, 2021)
CSNK2B has recently been implicated as a disease gene for neurodevelopmental disability (NDD) and epilepsy. Information about developmental outcomes has been limited by the young age and short follow-up for many of the previously reported cases, and further delineation of the spectrum of associated phenotypes is needed. We present 25 new patients with variants in CSNK2B and refine the associated NDD and epilepsy phenotypes. CSNK2B variants were identified by research or clinical exome sequencing, and investigators from different centers were connected via GeneMatcher. Most individuals had developmental delay and generalized epilepsy with onset in the first 2 years. However, we found a broad spectrum of phenotypic severity, ranging from early normal development with pharmacoresponsive seizures to profound intellectual disability with intractable epilepsy and recurrent refractory status epilepticus. These findings suggest that CSNK2B should be considered in the diagnostic evaluation of patients with a broad range of NDD with treatable or intractable seizures.

Xq22 deletions and correlation with distinct neurological disease traits in females: Further evidence for a contiguous gene syndrome. - Hijazi, Hadia; Coelho, Fernanda S; Gonzaga-Jauregui, Claudia; Bernardini, Laura; Mar, Soe S; Manning, Melanie A; Hanson-Kahn, Andrea; Naidu, Sakkubai; Srivastava, Siddharth; Lee, Jennifer A; Jones, Julie R; Friez, Michael J; et al. (Hum Mutat, 2020)
Xq22 deletions that encompass PLP1 (Xq22-PLP1-DEL) are notable for variable expressivity of neurological disease traits in females ranging from a mild late-onset form of spastic paraplegia type 2 (MIM# 312920), sometimes associated with skewed X-inactivation, to an early-onset neurological disease trait (EONDT) of severe developmental delay, intellectual disability, and behavioral abnormalities. Size and gene content of Xq22-PLP1-DEL vary and were proposed as potential molecular etiologies underlying variable expressivity in carrier females where two smallest regions of overlap (SROs) were suggested to influence disease. We ascertained a cohort of eight unrelated patients harboring Xq22-PLP1-DEL and performed high-density array comparative genomic hybridization and breakpoint-junction sequencing. Molecular characterization of Xq22-PLP1-DEL from 17 cases (eight herein and nine published) revealed an overrepresentation of breakpoints that reside within repeats (11/17, ~65%) and the clustering of ~47% of proximal breakpoints in a genomic instability hotspot with characteristic non-B DNA density. These findings implicate a potential role for genomic architecture in stimulating the formation of Xq22-PLP1-DEL. The correlation of Xq22-PLP1-DEL gene content with neurological disease trait in female cases enabled refinement of the associated SROs to a single genomic interval containing six genes. Our data support the hypothesis that genes contiguous to PLP1 contribute to EONDT.
Keywords: Child; Child, Preschool; Chromosome Breakpoints; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, X; Comparative Genomic Hybridization; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Nervous System Diseases; Pedigree; Phenotype; Quantitative Trait, Heritable; Repetitive Sequences, Nucleic Acid; Sex Factors; Syndrome; X Chromosome Inactivation